ON THE BIOLOGY OF THE FLAT MOUTHED CATFISH TACHYSURUS PLATYSTOMUS (DAY) FROM MANDAPAM - Menon, N Gopinatha (Indian Journal of Fisheries, 2011)
As determined from length-frequency studies, one-, two-, three- and fouryear- old fish respectively attain 178, 256, 310 and 366 mm size. As indicated by the opercular bone, the corresponding sizes were at 173,